Things I wish I told my mother - Patterson, Sue; DiLallo, Susan, 1947-; Patterson, James, 1947- (New York, NY : Little, Brown and Company, 2023)
Laurie surprises her mother, "Dr. Liz", with a mother-daughter vacation in Paris, France--one that brings to light a lifetime of secrets.
"A novel"--Page 1 of cover.
Keywords: Mothers and daughters -- Fiction; Vacations -- Fiction; Family secrets -- Fiction; Motherhood -- Fiction; Large type books; Family secrets; Large type books; Motherhood; Mothers and daughters; Vacations; Paris (France) -- Fiction; France -- Paris; Domestic fiction; Fiction; Large print books; Novels; Domestic fiction; Novels; Large print books